The Effect of Moral Reasoning and Environemental Attitudes on Environmental Accountability - AFDAL AFDAL (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to investigate the effect of moral reasoning and environmental attitudes (both ecocentric and anthropocentric) on environmental accountability. This paper argues that the higher the moral reasoning, the stronger the support for environmental accountability. Additionally, the paper argues that ecocentric support for environmental accountaility is stronger than anthropocentric support. The results show that moral reasoning has a significant positive effect on environmental accontability. Results also show that an ecocentric attitude is stronger than the anthropocentric attitude in supporting environmental accontability. The implication of these findings on the educational side is that, to increase support for the environment, education must increase students’ moral reasoning and ecocentric attitude. The implication on the corporate side is that, to increase the environmental accountability of a company, employees who have high moral reasoning and ecocentric attitudes must be recruited.